Changes in fetal Doppler indices as a marker of failure to reach growth potential at term. (March 2014) - Morales‐Roselló, J.; Khalil, A.; Morlando, M.; Papageorghiou, A.; Bhide, A.; Thilaganathan, B.
ABSTRACT Objective To evaluate whether changes in the middle cerebral artery (MCA), umbilical artery (UA) and cerebroplacental ratio (CPR) Doppler indices at term might be used to identify those appropriate‐for‐gestational‐age (AGA) fetuses that are failing to reach their growth potential (FRGP). Methods This was a retrospective cohort study of data obtained in a single tertiary referral center over a 10‐year period from 2002 to 2012. The UA pulsatility index (PI), MCA‐PI and CPR were recorded between 37+0 and 41+6 weeks within 14 days before delivery. The Doppler parameters were converted into multiples of the median (MoM), adjusting for gestational age, and their correlation with birth‐weight (BW) centiles was evaluated by means of regression analysis. Doppler indices were also grouped according to BW quartiles and compared using Kruskal–Wallis and Dunn's post‐hoc tests. Results The study included 11 576 term fetuses, with 8645 (74.7%) classified as AGA. Within the AGA group, fetuses with lower BW had significantly higher UA‐PI, lower MCA‐PI and lower CPR MoM values. Large‐for‐gestational‐age (LGA) fetuses were considered as the group least likely to be growth‐restricted. The CPR MoM < 5th centile (0.6765 MoM) in these fetuses was used as a threshold for diagnosing FRGP. Using this definition, in the AGA pregnancies the percentage of fetuses with FRGP was 1% in the 75–90th BW centile group, 1.7% in the 50–75th centile group, 2.9% in the 25–50th centile group and 6.7% in the 10–25th centile group. Conclusion AGA pregnancies may present with fetal cerebral and placental blood flow redistribution indicative of fetal hypoxemia. Fetal Doppler assessment may be of value in detecting AGA pregnancies that are subject to placental insufficiency, fetal hypoxemia and FRGP. Future studies are needed to evaluate the appropriate threshold for the diagnosis of FRGP and the diagnostic performance of this new approach for the management of growth disorders. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd